PENGARUH WORK LIFE BALANCE DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT BANK AGRONIAGA TBK CABANG BANDUNG - udin, Nafi (Sains Manajemen, 2015)
The objective from this research is to investigate the effect of work life balance and job satisfaction on employee turnover intention at PT Bank Agroniaga Tbk Bandung Branch.This type of research is descriptive and verification with descriptive survey and explanatory survey method. Data obtained from all employees PT Bank Agroniaga Tbk Bandung Branch, amounting to 30 people. The data was collected using a questionnaire instrument.The analytical method used is descriptive analysis that describes each variable in detail and with path analysis to determine the existence and simultaneous and partial influence between independent variables and dependent variable.The result of descriptive analysis shows that work life balance is perceived by the employee is good enough/ medium and job satisfaction felt by employees also has beenquite good, while the rate turnover intention experienced by the employees belonging to medium category, the result of path analysis and hypothesis indicate that work life balance and job satisfaction has influence in simultaneously and partial towards turnover intention